PENGARUH KONSELING PERSONAL DENGAN MEDIA FLIPBOOK TERHADAP PENGETAHUAN DAN SIKAP MASYARAKAT TENTANG PENCEGAHAN TUBERKULOSIS PARU DIWILAYAH KERJA PUSKESMAS PAKAN KAMIS KABUPATEN AGAM TAHUN 2024 - Maisyarah, Maisyarah; Satria, Eka Budi (HUMAN CARE JOURNAL, 2025)
Pulmonary TB disease that leaves suffering for public health, the disease is caused by Mycrobakterium Tubercolusis, Indonesia's incident rate reaches 301/100000 population, while in West Sumatra Province there are 37,063 suspected pulmonary TB cases, the results of the examination obtained 20,730 pulmonary TB sufferers, Agam Regency is one of the regencies in West Sumatra, the discovery of suspects examined was 2,426 people (26.2%) and cases found were 578 people (32.9%). in the working area of the Pakan Kamis Health Center, one of the Health Centers in Agam Regency, has a target of 616 suspects but 316 people were found and examined (51.3%) and 59 people were declared BTA Positive who became Pulmonary TB Cases. The purpose of the study was to determine the effect of the personal counseling method with flipbook media on Community Knowledge and Attitudes in efforts to prevent Pulmonary Tuberculosis in the work area of the Pakan Kamis Health Center, Agam Regency in 2024. The study was quantitative with a quasi-experimental design, namely the one group pre-post test design approach. The population in the study was 316 people, a sample of 20 people who were targeted by the study with univariate and bivariate analysis. The results showed that the average knowledge before (4.80) and after (9.65) attitudes before (27.15) and after (32.15) counseling, there was a difference in knowledge before and after (p = 0.000 <0.05), while in attitudes there was no effect of counseling with flipbook media (p = 0.438> 0.05). In an effort to increase public knowledge, Pakan Kamis Health Center health workers in providing education can use the personal counseling method with flipbook media.